Evaluations of the in vivo Laxative Effects of Aqueous Leaf and Stem Extracts of Artemisia Abyssinica in Mice - Ayele AG; Kawet JS (Dove Medical Press, 2024)
Akeberegn Gorems Ayele, Jeylan Sinba Kawet Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Akeberegn Gorems Ayele, Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Zambia Street, PO Box 9086, Addis Ababa, Ethiopia, Tel +251985408322, Email Akeberegn.gorems@aau.edu.etBackground: People frequently complain of long-term constipation. The cost associated with using modern medications to treat constipation is significant, and the probability of encountering side effects is notably high. These limitations restrict their effectiveness in therapy, remain unresolved, and underscore the need for research on alternative therapeutic approaches. Plants of the genus Artemisia have been used to treat constipation. Therefore, the aim of this study was to evaluate the laxative effects of aqueous A. abyssinica leaf and stem extracts of Artemisia abyssinica in mice.Methods: The laxative activity of A. abyssinica leaf and stem extracts was evaluated using three models: laxative activity, gastrointestinal motility, and gastrointestinal secretion. In this study, bisacodyl was used as a standard laxative and loperamide was used to induce constipation.Results: In the laxative test, 200 (P< 0.05) and 400 mg/kg (p< 0.01) doses of plant extract significantly increased the percentage of fecal water content. Moreover, the highest dose of extract increased the frequency of defecation after 12 h (p< 0.05). In the remaining two models, the experimental plans also showed significantly higher gastrointestinal motility and noticeable accumulation of intestinal fluid.Conclusion: The results of this study indicate that aqueous leaf and stem extracts of A. abyssinica have laxative effects.Keywords: laxative, constipation, Artemisia abyssinica, castor oil, loperamide